A Case Report of DVT following the Johnson and Johnson Vaccine against the Novel SARS-CoV-2. (17th May 2022) - Bangolo, Ayrton; Cherian, Jeffin; Ahmed, Mohamed; Atoot, Ali; Gupta, Bhavna; Atoot, Adam
Abstract : Deep vein thrombosis (DVT) is the formation of a blood clot typically in the deep veins of the extremities. The risk factors for venous thrombosis are primarily related to hypercoagulability, which can be genetic, acquired, or due to immobilization and venous stasis. The Johnson and Johnson (J&J) vaccine developed against the novel SARS-CoV-2 has been linked to more specific cases of thrombosis, associated with low platelet levels similar to that seen in heparin-induced thrombocytopenia. In this case report, we present a female who developed a DVT four days after receiving the J&J vaccine. We propose that the administration of this vaccine may further increase the risk of developing DVTs in patients with previous risk factors, and we hope to use this case to support screening all patients for previous risk factors for thrombosis before administration of the J&J vaccine.